2008
DOI: 10.4049/jimmunol.180.11.7318
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of B Cells in a Murine Model of Allergic Airway Disease

Abstract: Mice sensitized to ovalbumin (OVA) develop a biphasic response to OVA aerosols, such that acute exposure results in allergic airway disease (AAD) while chronic exposure results in local inhalational tolerance (LIT), with resolution of local pulmonary responses but persistence of the systemic allergic response. We have previously reported that B cell lymphocytosis persists in hilar lymph nodes (HLN) during LIT and that CD4+CD25+Foxp3+ Treg cells are significantly increased in the HLN of LIT mice. This raised th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 41 publications
8
83
1
1
Order By: Relevance
“…These data were consistent with previous reports indicating that Bregs must be activated to be effective (19). Moreover, consistent with other Bregs (15,16,30,31), TIM-1 + Bregs were antigen specific, since TIM-1 + B cells from mice receiving an unrelated (C3H) allograft were unable to prolong graft survival when transferred into JHD recipients of B6 islets ( Figure 6B). Likewise, transfer of TIM-1 + B cells from BALB/c mice exposed to B6 alloantigen protected JHD recipients from rejecting B6 islets, but not C3H islets (Supplemental Figure 3A).…”
Section: Tim-1 + B Cells Are Regulatory and Transfer Donor-specific Lsupporting
confidence: 82%
See 1 more Smart Citation
“…These data were consistent with previous reports indicating that Bregs must be activated to be effective (19). Moreover, consistent with other Bregs (15,16,30,31), TIM-1 + Bregs were antigen specific, since TIM-1 + B cells from mice receiving an unrelated (C3H) allograft were unable to prolong graft survival when transferred into JHD recipients of B6 islets ( Figure 6B). Likewise, transfer of TIM-1 + B cells from BALB/c mice exposed to B6 alloantigen protected JHD recipients from rejecting B6 islets, but not C3H islets (Supplemental Figure 3A).…”
Section: Tim-1 + B Cells Are Regulatory and Transfer Donor-specific Lsupporting
confidence: 82%
“…Bregs have previously been implicated in amelioration of allergic airway disease (31)(32)(33). Adoptive transfer of TIM-1 + , but not TIM-1 -, B cells from mice with OVA-induced local inhalational tolerance, markedly reduced OVA-induced allergic airway disease in JHD recipients, as determined by reduced BAL leukocytosis, tissue inflammation, and bronchiolar goblet cell hyperplasia (Supplemental Figure 4), thus confirming our results in an independent model.…”
Section: Tim-1 + B Cells Are Regulatory and Transfer Donor-specific Lsupporting
confidence: 78%
“…Sublingual antigen challenge, a strategy for inducing oral tolerance, was partially impaired in B cell-deficient mice through a mechanism that depended on induction of FoxP3 + Tregs (113). In a separate study, repeated nasal antigenic challenge of mice induced a regulatory B-cell population in the local draining lymph node that suppressed lung inflammation and asthma in recipient ovalbumin (OVA)-sensitized mice after adoptive transfer (114). The effectiveness of these regulatory B cells was linked to B-cell expression of TGFβ but not IL-10 and the accumulation of FoxP3 + Tregs in the lung mucosa and local lymph nodes.…”
Section: B-cell Interactions With Regulatory T-cell Populationsmentioning
confidence: 99%
“…Previous studies using chronic allergen challenge models showed an expansion of Treg (44,45). The expansion includes actual proliferation of Treg in response to chronic Ag stimulation and also peripheral conversion of Teff to Treg under appropriate environmental cues, such as the presence of TGF-␤ and dendritic cell-derived retinoic acid, inhibited costimulation or IL-2 production, and the presence of subimmunogenic Ag conditions (46 -50).…”
Section: Treg Inhibit Angiogenesis Of Airway Remodeling Via Dll4-notcmentioning
confidence: 96%